Analisis Pengaruh Peranan Perempuan dalam Pertumbuhan Ekonomi di Provinsi Jawa Tengah Tahun 2018-2022 - Az-zahro, Annisa Amalia; Aisyah, Siti (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
Gender roles that are detrimental to women can impact economic growth. This study aims to determine the extent to which the women's labor force participation rate, average years of women education, women's life expectancy, the gender empowerment index, and the gender inequality index influence economic growth in Central Java Province from 2018 until 2022 by employing panel data regression analysis techniques. The results of this study indicate that life expectancy has a significant impact on economic growth, as improved health leads to higher productivity. The inclusion of gender empowerment index variables and gender inequality index distinguishes this study from previous research. This research emphasizes women's empowerment by disseminating information to the community regarding the significance of gender equality.